Effect of e-service quality towards customer satisfaction in online shopping among Y Generation at UTeM / Norquzaiman Azhar - Azhar, Norquzaiman (Faculty of Business and Management, 2016)
In this study, it analyzed the effect of e-service quality towards customer satisfaction in online shopping among Y generation. The number of online retailers in Malaysia has shown a rapid growth in recent years. However, based on previous researcher. The study was gathered using 150 set of questionnaires as it was distributed at University Technical Malaysia (UTeM) Malacca City Campus. The data were interpreted using multiple regression analysis to explain the relationship on how web design, security, information quality and responsiveness affect customer satisfaction. The most factors that influence the agent’s retention were security and followed by web design, responsiveness and information quality. Overall, there were significant relationship between dependent variable and independent variables. Based on this study, it is good to understanding the factor that influence customer satisfaction toward customer satisfaction.